Hydroxychloroquine and sulphasalazine alone and in combination in rheumatoid arthritis: a randomised double blind trial. Issue 10 (October 1993) - Faarvang, K L; Egsmose, C; Kryger, P; Pødenphant, J; Ingeman-Nielsen, M; Hansen, T M
Abstract : OBJECTIVES--To compare the effects of hydroxychloroquine and sulphasalazine alone and in combination in rheumatoid arthritis. METHODS--A six month randomised, multicentre, double blind trial with three parallel groups was performed. Ninety one outpatients with active rheumatoid arthritis were included. Monthly assessments of erythrocyte sedimentation rate, morning stiffness, number of swollen joints, a pain score, and global assessments were carried out. Radiographs of hands and wrists were taken before and after the trial. RESULTS--Sixty two patients completed the study. The 29 withdrawals caused no evident bias, and there was no difference in side effects among the three groups. All variables improved significantly with time. Patients treated with a combination of hydroxychloroquine and sulphasalazine responded better and faster than those treated with hydroxychloroquine alone, but there was no statistically significant difference between the combination treatment and single drug treatment with sulphasalazine or between treatment with hydroxychloroquine and sulphasalazine given alone. CONCLUSION--The present results do not support a recommendation to use a combination of hydroxychloroquine and sulphasalazine in the treatment of rheumatoid arthritis.